P228 Is the brompton bpat a useful tool to assess breathing pattern disorder in asthma?. (15th November 2016) - Todd, SJ; Livingston, R; Grillo, L; Menzies-Gow, A; Hull, J
Abstract : Introduction: Breathing pattern disorder (BPD) is a prevalent cause for persistent dyspnoea in patients with asthma. The diagnosis of BPD is difficult and currently relies exclusively on subjective assessment with no reliable diagnostic tools currently validated to support a clinical assessment. Aim: To determine if the Brompton Breathing Pattern Assessment Tool (BPAT) has value in the assessment of BPD. Method: We audited an objective scoring tool, the BPAT, in patients with asthma and/or unexplained dyspnoea completing a systematic multi-disciplinary assessment. The BPAT (score 0 to 14) evaluates aspects of breathing (including; rate, flow, pattern, rhythm and air hunger). This was compared against BPD diagnosis made by current MDT practise. BPAT measures were also compared with indices of dyspnoea/disease control; e.g. walking test, Dyspnoea 12 (D12), Nijmegen and Asthma Quality of Life Questionnaire (AQLQ). Results: 75 patients; n = 54 females, were divided into 3 groups by diagnosis (asthma, asthma+BPD and BPD alone). BPAT was statistically significantly different between all groups (Table). It also correlated statistically significantly with both the D12 score (r = 0.586, N = 23, p = 0.003) and Nijmegen score (r = 0.418, N = 24, p = 0.042) in the BPD group. There was no relationship between BPAT and FEV1 % predicted or 6MWT distance. Conclusion: The BPAT score was higher in those patients diagnosed with BPD both with and without asthma. The BPAT score also correlates with both the D12 and Nijmegen score in patients diagnosed with BPD. This suggests it detects and characterises common aspects of BPD. Further work is now needed to validate the BPAT and determine its responsiveness to intervention.